Survival Predictors in Pulmonary Arterial Hypertension Patients Undergoing Balloon Pulmonary Angioplasty - Khan, Farhat Ullah; Afzal, Zeeshan; Akhtar, Syed Ahsan; Hafeez, Muhammad; Khan, Tashfeen Irtaza (Indus Journal of Bioscience Research, 2025)
Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a severe complication of pulmonary embolism that leads to progressive right heart failure and death if untreated. Balloon pulmonary angioplasty (BPA) has emerged as a promising intervention for patients with inoperable or residual disease post-pulmonary endarterectomy. Objective: To identify predictors of short-term survival in pulmonary arterial hypertension patients undergoing BPA. Materials and Method: This prospective observational study was conducted at Department of Cardiology, Hayatabad Medical Complex, Peshawar from January, 2023 to June 2023. Fifty-two patients with confirmed inoperable or residual CTEPH underwent BPA. Hemodynamic and clinical parameters were assessed pre- and post-procedure, and survival was evaluated at six months. Results: Survival at six months was 88.5%. Post-procedural mean pulmonary artery pressure <35 mmHg, baseline cardiac index ≥2.0 L/min/m², and absence of vascular injury during BPA were independent predictors of survival. Significant improvements were observed in mPAP, PVR, and WHO functional class. Conclusion: BPA significantly improves survival and clinical status in selected PAH patients. Early hemodynamic response and procedural safety are key survival predictors.